ONLIFE VERSUS ONLINE: THE ROLE OF THEATER IN THE POST-PANDEMIC ERA - Garavaglia , Valentina (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
It is known how deeply the live entertainment sector has been affected by the pandemic crisis: Covid 19 has had a strong impact on the entire system, canceling a large part of live activities and increasing the transition towards the use of digital products. However, as emerges from the data, following the emergency situation, Italy has started organizing events and attending theaters again. The lockdown has revealed how damaging the deprivation of live relationships, especially among young people, can be, and therefore how precious and irreplaceable the relational activity that is the basis of any experience can be, especially in the age of education. theatrical, because man work on himself and self-care cannot ignore the relationship with others. The theater is the place of relationships. An excellent diagnostic tool for understanding group dynamics and the type of communication and problems that everyone has with others. Being a place where relationships are built and discovered, it is also therapeutic and socializing by its nature. In the protected space of the theater, daily rituals are innovated, and ideas and projects are born for the change not only of the individual, but of society itself. Two projects of the IULM University (International University of Languages and Media) are an example of this: Teatro Formazione Società and Mondo Acrobata.